Assistance for the Furudul Ainiyah Program to Improve the Quality of Madrasah Graduates - Izzatul Munawwaroh; Febriyanti Ghayatul Qushwa; Hasan Baharun; Hefniy Hefniy; Moh Tohet (Communautaire: Journal of Community Service, 2024)
This study explores the implementation of the Furudul Ainiyah mentoring program in an effort to improve the quality of graduates at Madrasah Aliyah. The Furudul Ainiyah program, which is designed to strengthen students' understanding and basic skills, has significant potential in improving the quality of education. However, madrassas often face challenges related to program implementation, including a lack of resources, varied teaching methodologies, and infrastructure support. The research method uses a qualitative approach with case studies as the main framework. Data was collected through in-depth interviews, classroom observations, and analysis of curriculum documents and student evaluation results. The results of the study show that the assistance of the Furudul Ainiyah program has succeeded in improving students' understanding of the subject matter and their academic skills. The program also helps improve the learning process by strengthening academic support and increasing student engagement. However, the challenges faced include the need for further training for teachers and the improvement of support facilities.